Net primary productivity in a Tropical Dry Forest of northern Colombia - Aguirre-Forero, Sonia Eperanza; Rozo-Celemín, Arturo; Piraneque-Gambasica, Nelson Virgilio (Revista de Ciencias Agrícolas, 2024)
Tropical dry forests are the world’s second most relevant forest type, home to unique vegetation and highly threatened by human activity. This study aimed to determine changes in plant biomass within a tree-hectare permanent plot of tropical dry forest (TDF) at the Universidad del Magdalena over 12 months. The composition, structure, and plant dynamics were characterized using drone imagery and allometric equations for dry climates. Biomass was calculated for 848 trees and shrubs with a diameter at breast height (DBH) over 10 cm, and a Normalized Difference Vegetation Index (NDVI) time series was established. It was possible to identify the change in NDVI with a positive trend in areas with higher soil moisture, higher coverage, vegetation network, and limited access. Likewise, the findings show that areas with lower coverage have greater accessibility and lower diversity. The vegetation cover dynamics within the Universidad del Magdalena’s TDF plot revealed low variability in NDVI over the study period, with values exceeding 0.7 in 58% of observations, reflecting a linear trend with the rainy seasons. Estimating the vegetal cover biomass is feasible using differentiated indices and techniques that reduce costs and time and do not have destructive implications for the vegetation.